Observational Study of Tax Compliance and Tax Evasion in Nigeria - Ogunshola Idowu Bello; Karina Kasztelnik (Financial Markets, Institutions and Risks)
This paper summarizes the arguments and counterarguments within the scientific discussion on tax evasion. The main purpose of the research is to explore how leaders in the manufacturing industries could understand the drivers of tax evasion in manufacturing companies, which may prevent sanctions from tax authorities in Lagos State, Nigeria. Systematization of the literary sources and approaches for solving the problem of low tax revenues indicated the presence of a significant number of drivers of tax evasion. The relevance of this scientific problem decision is that high levels of tax evasion can lead to a decrease in tax revenues to such an extent that it will threaten the ability of the Nigerian government to finance fiscal measures. Investigation of the topic of tax evasion in the paper is carried out in the following logical sequence: at the first stage, an analysis of taxpayers; compliance attitude in developing countries and the level of tax compliance and tax evasion was conducted. In the second stage, factors affecting tax compliance and factors influencing tax evasion were summarized and analyzed in the article, and the economic consequences of these processes were determined. Methodological tools of the research methods were the methods of generalization, analysis, and synthesis of scientific literature, formalization, and abstraction. The object of research is the theories and/or concepts of tax evasion, in particular: the theory of reasoned action and the theory of technology adoption life cycle. The article presents the results of an empirical analysis of the drivers of tax evasion, which proved that manufacturing companies deliberately fail to submit the required tax return documentation to avoid tax obligations. The study empirically confirms and theoretically proves that the list of drivers of tax evasion may also include other reasons for tax evasion for manufacturing companies, such as a lack of education and understanding of the tax documentation requirements, process issues, technology access issues, and others. The results of the research can be useful for the tax authorities in Lagos to educate other sectors that engage in tax evasion to increase the rate of overall tax compliance.